Molecular docking and proteomics reveals the synergistic antibacterial mechanism of theaflavin with β-lactam antibiotics against MRSA - Guan, Shuhan; Zhong, Ling; Yu, Hangqian; Wang, Li; Jin, Yajing; Liu, Jingyu; Xiang, Hua; Yu, Hao; Wang, Lin; Wang, Dacheng (Frontiers in Microbiology, 2022)
Recurrent epidemics of methicillin-resistant Staphylococcus aureus (MRSA) have illustrated that the effectiveness of antibiotics in clinical application is rapidly fading. Because of the current lack of antibiotic development, a feasible approach is to combine natural products with existing antibiotics to achieve an antibacterial effect. In our molecular docking study, we found that theaflavin (TF) preferentially enter deeply into the allosteric site of penicillin-binding protein 2a (PBP2a), inducing the PBP2a active site to open, which is convenient for β-lactam antibiotics to treat MRSA infection, instead of directly exerting antibacterial activity at the active site. Subsequent TMT-labeled proteomics analysis showed that TF treatment did not significantly change the landscape of the Staphylococcus aureus (S. aureus) USA300 proteome. Checkerboard dilution tests and time-kill curve assays were performed to validate the synergistic effect of TF and ceftiofur, and the fractional inhibitory concentration index (FICI) was 0.1875. The antibacterial effect of TF combined with ceftiofur was better than that of single-drug treatment in vitro. In addition, TF effectively enhanced the activity of ceftiofur in a mouse model of MRSA-induced pneumonia. Our findings provide a potential therapeutic strategy to combine existing antibiotics with natural products to resolve the prevalent infections of multidrug-resistant pathogens. TF, as a new candidate compound, can be combined with β-lactam antibiotics against MRSA infections.